2014
DOI: 10.1080/01596306.2013.871229
|View full text |Cite
|
Sign up to set email alerts
|

The power of one? Conditions which challenge managerial professional development practices

Abstract: This paper draws upon Bourdieu's (1984) concepts of habitus, capital and field to better understand and appreciate the conditions which encouraged the productive professional development practices of one very capable teacher working in a secondary school in the British Midlands. Rather than celebrating this teacher's practices and perspective as evidence of the capacity of the heroic individual to overcome sometimes adverse circumstances, the paper reveals how the experiences of this teacher can be understood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As well, teachers already confident in technology have reported that they still need time to practice integrating it effectively (Sadaf, Newby, & Ertmer, 2012) Staff development leaders must begin to provide more opportunities within the meetings and trainings for staff to discuss best practices and pedagogy in addition to instruction led by technology. The more open discussion, the better received professional development will be (Hardy, 2014). This open dialogue will benefit everyone because it will promote asking questions which can enhance inquiry and strengthen teacher practice (Aritz, Walker, Cardon, & Zhang, 2017;Nicholson, Capitelli, Richert, Bauer, & Bonetti, 2016).…”
Section: Learning Opportunities: Trainings and Mentorshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…As well, teachers already confident in technology have reported that they still need time to practice integrating it effectively (Sadaf, Newby, & Ertmer, 2012) Staff development leaders must begin to provide more opportunities within the meetings and trainings for staff to discuss best practices and pedagogy in addition to instruction led by technology. The more open discussion, the better received professional development will be (Hardy, 2014). This open dialogue will benefit everyone because it will promote asking questions which can enhance inquiry and strengthen teacher practice (Aritz, Walker, Cardon, & Zhang, 2017;Nicholson, Capitelli, Richert, Bauer, & Bonetti, 2016).…”
Section: Learning Opportunities: Trainings and Mentorshipsmentioning
confidence: 99%
“…Trainings, professional development, and mentorships must provide more opportunities within meetings for active discourse among all participants. The greater open discussion opportunities, the better-received learning opportunities will be (Hardy, 2014). This open dialogue will benefit everyone because it will promote asking questions which can enhance inquiry and strengthen teacher practice (Artiz et al 2017;Nicholson et al, 2016).…”
Section: Learning Opportunities: Trainings and Mentorshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reveal that at the same time as teachers were actively involved in their learning, and supportive conditions were in evidence to enhance their learning, work intensification, stress, strong competition between teachers and schools were also evident in the context of increasingly market-oriented and managerialist approaches to schooling. This intensification is exacerbated by more globalised, neoliberal conditions within which teachers' work is unfolding (Ball, 2012), and which focuses attention on academic performance, particularly competitive testing, and numeric conceptions of that performance (Connell, 2013;Hardy, 2014;Hardy, 2015).…”
Section: The State Of the Field Of Teacher Learning And The Conditionmentioning
confidence: 99%